MUTISME AKINETIK AKIBAT OKLUSI BILATERAL ARTERI SEREBRI ANTERIOR - Parningotan Yosi Silalahi, Anak Agung Bagus Ngurah Nuartha, Ida Bagus Kusuma Putra (NEURONA, 2012)
INTRODUCTION AKINETIK MUTISM DUE TO BILATERAL LESIONS OF THE ANTERIOR FRONTAL LOBES ARE RARE AND THEREFORE HAS NOT REPORTED STATISTICS